2022
DOI: 10.1002/jum.15972
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Ultrasound‐Guided Incisional Biopsy Enhances the Pathological Accuracy of Incisional Biopsy of Cutaneous Melanoma

Abstract: Objectives-To assess the feasibility of preoperative ultrasound (US)-guided incisional biopsy through a prospective controlled clinical trial.Methods-This was a prospective, double-arm, single-center study of Chinese patients. Thirty patients were enrolled in the study. Fourteen patients received incisional biopsies for which the choice of biopsy area relied on a clinical evaluation, and 16 patients received incisional biopsies for which the choice of biopsy area relied on a US-guided evaluation. The following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This is the most lethal cutaneous tumor, and ultrasound can support the detection of the primary tumor, its extent, including depth; therefore, it is possible to provide an ultrasonographic Breslow index of the cutaneous melanoma. 6,24,37,38,73,[87][88][89][90][91] On ultrasound, they tend to show as oval or fusiform-shaped, hypoechoic dermal or hypodermal lesions. However, deep melanomas may appear as bulky masses with prominent hyperechogenicity of the surrounding hypodermis due to edema.…”
Section: Melanomamentioning
confidence: 99%
See 3 more Smart Citations
“…This is the most lethal cutaneous tumor, and ultrasound can support the detection of the primary tumor, its extent, including depth; therefore, it is possible to provide an ultrasonographic Breslow index of the cutaneous melanoma. 6,24,37,38,73,[87][88][89][90][91] On ultrasound, they tend to show as oval or fusiform-shaped, hypoechoic dermal or hypodermal lesions. However, deep melanomas may appear as bulky masses with prominent hyperechogenicity of the surrounding hypodermis due to edema.…”
Section: Melanomamentioning
confidence: 99%
“…On color or power Doppler, they tend to present prominent vascularity with low-velocity vessels (Figure 12). 6,24,37,38,73,[87][88][89][90][91] It is possible to perform a locoregional staging of the melanoma that includes the detection of satellite (<2 cm from the primary tumor), in-transit (≥2 cm from the primary tumor), and nodal metastasis. 37,38,87,88,90 Metastatic lymph nodes of melanoma commonly present a round shape, prominent hypoechogenicity with loss of the hyperechoic medulla, and chaotic cortical vascularity.…”
Section: Melanomamentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, such an inspection cannot be performed using devices with a probe frequency of 20 MHz or higher. In our previous research, we observed that the utilization of the 18MHz probe resulted in improved localization during incisional biopsies in patients with AM ( 16 ). This finding suggests that the use of the 18MHz probe can aid in accurately identifying the target area for biopsy, facilitating more precise and targeted sampling of the lesion.…”
Section: Discussionmentioning
confidence: 97%